Emergency anesthetic care complexities in the elderly - Evangelina Dávila Cabo de Villa; Omar Rojas; Juana María Morejón Fernández; Belkys Mercedes Vicente Sánchez; Olga Lidia Sánchez Sarría (Medisur)
Aging is a universal nature long process, typical of living beings. Its growth at the world population level is notorious and it is not exclusive to developed countries. The elderly patient presents great challenges due to the alterations caused by the aging process, which is accompanied by decreased response capacity with uneven deterioration of a series of morphophysiological, psychological and biochemical functions. On the other hand, medical care for patients with urgent surgical conditions unleashes challenges for the work team due to the need to provide the patient with assistance with a minimum of preparation, which entails identifying a state of health in an acceptable period of time, achieve stabilization prior to the surgical act and favor a satisfactory recovery. For these reasons, this bibliographical review was carried out to highlight a series of factors that take part in the aging process and its implications for the anesthetic procedure.